Drill Training Program to Improve Badminton Forehand Smash Skills - Asyari, Ego Bayu; Subekti, Nur (Universitas Muhammadiyah Surakarta, 2023)
This research aims to find out whether the drill training program has an effect on improving badminton forehand smash skills. This research method uses a quantitative type of research with an experimental research design, one group pretest - posttest design. This research was carried out at the Karanglo sports building, RT 04/RW 04, Waru, Baki District, Sukoharjo Regency, Central Java, on October 18 2023. The subjects in this research were all 61 members of the UMS sports education badminton talent team, totaling 61 people. with a sample of 20 people, and this sampling technique used Purposive Sampling. The results of this research were tested statistically using SPSS 23, obtaining a calculated t value = -10.576 < t table = - 2.093 and a significance value of 0.00, which means the p value < 0.05, meaning there is an influence of the drill training program to improve badminton forehand smash skills.